Cross-modal plasticity among sensory networks in neuromyelitis optica spectrum disorders. (June 2019) - Rocca, Maria Assunta; Savoldi, Filippo; Valsasina, Paola; Radaelli, Marta; Preziosa, Paolo; Comi, Giancarlo; Falini, Andrea; Filippi, Massimo
Objective: To explore resting-state (RS) functional connectivity (FC) of the main sensory/motor networks of patients with neuromyelitis optica spectrum disorders (NMOSDs), clinically isolated optic neuritis (ON), and myelitis. Methods: Clinical evaluation and RS fMRI were obtained from 28 NMOSD, 11 recurrent ON, and 12 recurrent myelitis patients and 30 healthy controls. Between-group RS FC comparisons and correlations with motor performance were assessed (SPM12) on the main sensory/motor RS networks (RSNs) identified by independent component analysis. Functional network connectivity analysis estimated inter-network connectivity. Results: Intra- and inter-network RS FCs were reduced in RSNs associated to somatosensory modalities affected by pathology: regions of the primary visual network in ON patients, of the sensorimotor networks in myelitis patients, and of the sensorimotor and secondary visual networks in NMOSD patients. The opposite trend was observed in regions of RSNs spared by pathology: the auditory and part of visual networks in NMOSD, the secondary visual and sensorimotor networks in ON, and the primary visual network in myelitis patients. Better motor performance correlated with higher RS FC of spared RSNs. Conclusion: Sensory and motor RSN abnormalities occur in NMOSD. Loss of function within disease–target networks may elicit cross-modal plasticity across sensory networks potentially preserving clinical function.